Analyzing the Influence of Environmental Awareness and Financial Performance in the Desire for Sustainabilitiny Investing in Indonesian Investors - Brilyanputra Firjatullah Wahyu; Rofikoh Rokhim (GoAcademica Research & Publishing, 2023)
With the development of policies and attention in maintaining environmental sustainability with the phenomenon of global warming and climate change which is an important issue now, this study aims to analyze the priorities of Indonesian investors in investing and its effects in trading activities, the first stage is a comparative study of trading volume variables between issuers that prioritize sustainability and issuers that prioritize the financial side, the first stage will be analyzed by linear regression method independent t-test aims to see if there is a significant difference based on historical trading volume data of both groups of issuers. In the second stage, environmental awareness and financial performance variables are used to see which variable is the biggest influence in investors' choice of investment. A qualitative approach will be used in this study and multiple linear regression will be used to conduct hypothesis testing, data collection will be conducted using an online questionnaire. It was found that investors' preference is now for sustainable investment over conventional, with the most influential factor being financial performance. The results of the qualitative research are supported by the results of quantitative research which found that trading volume activity for sustainable issuers is increasing in the period 2023 and trading volume activity for conventional issuers is decreasing in the period 2023 The findings of this study aim to help other companies to see the importance of environmental awareness factors in front of the eyes of young investors.